Sociolinguistic factors affecting performance in the Clinical Skills Assessment of the MRCGP: a mixed methods approach - Hawthorne, Kamila; Roberts, Celia; Atkins, Sarah (Royal College of General Practioners, 2017)
Background: Differential performance in clinical skills assessments is a widespread phenomenon, for which there remain few explanations.